Redução de arrasto em escoamento monofásico e bifásico (líquido-líquido) com adição de polímeros solúveis em água e hidrocarbonetos - Barbosa, Kelvin Cristien de Oliveira (2025)
This work presents an experimental study on drag reduction (DR) in single-phase and liquid-liquid two-phase turbulent flows through the addition of polymers. The literature contains studies on drag reduction in two-phase flows; however, most investigations focus on gas-liquid flows or liquid-liquid flows with the polymer dissolved in the aqueous phase. In various industrial sectors, two-phase flow is a common occurrence, particularly in the oil and gas industry, where one of the main objectives is to enhance production flow rates. Consequently, there is growing interest in studying the effects of drag-reducing polymer additives in two-phase flows. The objective of this study is to evaluate the effect of polymers (soluble in both water and hydrocarbons) on pressure gradient reduction (drag reduction) and to analyze polymer degradation in single-phase and liquid-liquid two-phase flows. A water-soluble polymer (Diutan Gum 3 DG) and a hydrocarbon-soluble polymer (Polyisobutylene 3 PIB) with three different molecular weights are used. For the hydrocarbon-soluble polymer, rheological characterization, preliminary DR tests in single-phase flows, and degradation analysis for the three molecular weights are performed. As expected, drag reduction increases with higher polymer concentration and molecular weight. In two-phase flow experiments, the flow pattern is dispersed due to high flow rates. The effects of DG and PIB solutions are analyzed separately and in combination. It is concluded that drag-reducing additives are more effective in the dominant phase, meaning that the water-soluble additive is effective for water fractions greater than 0.5, while the hydrocarbon-soluble additive is effective for water fractions below 0.5. As expected, increasing DG concentration results in higher DR; however, an increase in flow rate when using only DG does not lead to further DR improvement. On the other hand, for PIB, an increase in flow rate results in greater DR. When both phases contain additives, a reduction in pressure is observed compared to the case without additives across the entire range of water fractions. Additionally, it is noted that at low concentrations (low water fractions), water droplets also contribute to drag reduction. PIB degradation increases as the total two-phase flow rate rises and is further intensified when the aqueous phase is also treated with additives